Fault Seal Integrity Assessment of the Bornu Basin Using Advanced Software Techniques - Didi, Chekwube Nnamdi (Earth and Planetary Science, 2025)
The Bornu Basin, located in northeastern Nigeria, is a sub-basin of the larger Chad Basin and has long been considered a prospective area for hydrocarbon exploration. Despite the presence of quality source rocks, favorable reservoir properties, and structural traps, exploration efforts have largely resulted in dry wells. This study investigates the fault seal integrity of the Bornu Basin as a potential explanation for this paradox. Using 3D seismic data and well logs from the Bulte-1 well, fault seal analysis was conducted with Move and Petrel software (2018 versions). Key techniques included the interpretation of fault geometries, stratigraphic modeling, and quantitative analyses such as Shale Gouge Ratio (SGR), Shale Smear Factor (SSF), Probabilistic SSF, Clay Smear Potential (CSP), and Hydrocarbon Column Height (HCCH) estimations. The F13 fault was identified as a regional structure of interest, and detailed analyses revealed heterogeneous sealing behavior along its plane. Results show that while some intervals demonstrate high sealing potential (high SGR and low permeability), other segments, particularly at greater depths, exhibit high fault throw, low smear continuity, and high leakage risk. These findings suggest that fault-related leakage and early hydrocarbon migration, possibly induced by tectonic or magmatic activity, are key factors limiting successful hydrocarbon entrapment in the basin. The study concludes that fault seal integrity is a critical risk factor in the Bornu Basin, and integrating advanced fault modeling into exploration workflows is essential for future prospect evaluation. ER